We had a hunch : a mystery - Ryan, Tom, 1977 February 26- (Atlantic Crime, 2025)
"Nancy Drew meets Yellowjackets in We Had a Hunch-a lively and suspenseful mystery from USA Today bestseller Tom Ryan that asks a simple question: what happens to your favorite teenage detectives when they grow up? Few stories captured the public's imagination in the year 2000 like the friendly rivalry between the Teen Detectives of Edgar Mills, Massachusetts. Twin sisters Alice and Samantha Van Dyne were thrust into the spotlight when they helped their father Police Chief Bill Van Dyne bust a dangerous drug smuggling ring. Across town, bookish Joey O'Day proved himself to be a talented investigator of a different sort when he used his computer skills to expose an online grifter preying on elderly victims. As the two sets of teenage sleuths began jockeying to outdo each other, they became a sensation, appearing on talk shows and the covers of teen magazines. But when a brutal series of murders rocked Edgar Mills, a deadly miscalculation on the part of the Van Dyne twins led to the shocking and gruesome deaths of both their father and Alice's boyfriend. The killer, Bruce Phillip Kershaw-better known as The Janitor-was ultimately captured, but both Edgar Mills and their beloved Teen Detectives would never be the same. It's been a quarter century since The Janitor terrorized Edgar Mills, and the Teen Detectives have grown up. Samantha and Joey have scattered: Sam to Los Angeles and a life as a B List reality TV star, and Joey to a lucrative tech career in Boston. Alice, on the other hand, still lives in Edgar Mills, rooted by her guilt and heartbreak. When Edgar Mills is shaken by a new murder that matches The Janitor's M.O., Kershaw offers, from his maximum-security prison cell, to provide information that could help crack this new case. The catch? He'll only talk to the teen detectives that put him away"-- Provided by publisher.